The Importance of Bank Storage in Supplying Baseflow to Rivers Flowing Through Compartmentalized, Alluvial Aquifers. Issue 12 (15th December 2017) - Rhodes, Kimberly A.; Proffitt, Tiffany; Rowley, Taylor; Knappett, Peter S. K.; Montiel, Daniel; Dimova, Natasha; Tebo, Daniel; Miller, Gretchen R.
Abstract: As water grows scarcer in semiarid and arid regions around the world, new tools are needed to quantify fluxes of water and chemicals between aquifers and rivers. In this study, we quantify the volumetric flux of subsurface water to a 24 km reach of the Brazos River, a lowland river that meanders through the Brazos River Alluvium Aquifer (BRAA), with 8 months of high‐frequency differential gaging measurements using fixed gaging stations. Subsurface discharge sources were determined using natural tracers and End‐Member Mixing Analysis (EMMA). During a 4 month river stage recession following a high stage event, subsurface discharge decreased from 50 m 3 /s to 0, releasing a total of 1.0 × 10 8 m 3 of water. Subsurface discharge dried up even as the groundwater table at two locations in the BRAA located 300–500 m from the river remained ∼4 m higher than the river stage. Less than 4% of the water discharged from the subsurface during the prolonged recession period resembled the chemical fingerprint of the alluvial aquifer. Instead, the chemistry of this discharged water closely resembled high stage "event" river water. Together, these findings suggest that the river is well connected to rechargeable bank storage reservoirs but disconnected from the broader alluvial aquifer. The average width of discrete bank storage zones on each side of the river, identified with Electrical Resistivity Tomography (ERT), was approximately 1.5 km. In such highly compartmentalized aquifers, groundwater pumping is unlikely to impact the exchange between the river and the alluvium. Plain Language Summary: Groundwater supplies baseflow to rivers sustaining their levels during droughts. Sustained river flows are critically important for riverine and estuarine ecosystems and for human consumption, farming and industrial uses. It is important to understand the timing and source of baseflow. Rivers which flow through alluvial aquifers with shallow water tables are commonly assumed to be well connected to the alluvial aquifer. If the alluvial aquifer is well‐connected to the river, large volumes of baseflow would be available to sustain river flows during long dry periods. In such a well‐connected river‐aquifer system, pumping for irrigation may decrease baseflow. In this study we uncover the timing and source of baseflow to the Brazos River during a prolonged dry period following a major high flow event along a 24 km reach. Practically all the water released to the river was chemically similar to dilute river water, stored in the banks during the high flow event. Negligable amounts of baseflow were derived from the alluvial aquifer. After two months of dry conditions, baseflow decreased to zero even while the alluvial aquifer water table remained high. Baseflow to many lowland rivers may be primarily derived from short‐term bank storage and not from the broader aquifer. Key Points: Subsurface water discharge was measured along a 24 km reach of a low‐gradient, coastal river over 8 months using fixed gaging stations Subsurface discharge decreased over 4 months of dry conditions following a flood while the water table in the alluvial aquifer remained high Natural tracers suggested that the subsurface discharge was composed of event water stored in the river banks and not from the alluvial aquifer